2017
DOI: 10.1016/j.drugalcdep.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptor M 4 positive allosteric modulators attenuate central effects of cocaine

Abstract: These findings further support the notion that M receptors are promising targets for the treatment of cocaine addiction, by showing that results can be replicated using distinct ligands, and that in addition to blocking reinforcing effects of cocaine relevant to ongoing drug taking, M positive allosteric modulators can also attenuate subjective and conditioned effects relevant to relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
(54 reference statements)
3
15
0
Order By: Relevance
“…Effects of M 4 receptor blockade on cocaine's S D effects have not been reported previously, but our findings are consistent with a report that tropicamide increased or prolonged cocaine-induced stereotypies in rats [52]. The notion that blocking either M 1 receptors or M 4 receptors increases effects of cocaine is also consistent with our findings that, conversely, pharmacological stimulation of M 1 and/or M 4 receptors attenuated the S D effects and reinforcing effects of cocaine in rats and mice ([2-5]; [6]). Taken together, this first data set suggests that M 1 and/or M 4 receptor blockade at least partly mediate the effects of scopolamine in the cocaine discrimination assay.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Effects of M 4 receptor blockade on cocaine's S D effects have not been reported previously, but our findings are consistent with a report that tropicamide increased or prolonged cocaine-induced stereotypies in rats [52]. The notion that blocking either M 1 receptors or M 4 receptors increases effects of cocaine is also consistent with our findings that, conversely, pharmacological stimulation of M 1 and/or M 4 receptors attenuated the S D effects and reinforcing effects of cocaine in rats and mice ([2-5]; [6]). Taken together, this first data set suggests that M 1 and/or M 4 receptor blockade at least partly mediate the effects of scopolamine in the cocaine discrimination assay.…”
Section: Discussionsupporting
confidence: 93%
“…The data are in agreement with the notion that stimulation of M 1 receptors and M 4 receptors can each attenuate the S D effect of cocaine, not only through direct pharmacological stimulation as shown previously ([2, 5]; [6]), but also through increased cholinergic tone due to blockade of M 2 autoreceptors. Finally, the findings also suggest that the cocaine-modulating effects of muscarinic receptor manipulations are likely not mediated entirely in the nucleus accumbens, but involve dorsal striatum or other brain regions as well.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Muscarinic receptors have long been known to play important roles in memory and cognitive functions, with muscarinic receptor antagonists like scopolamine being powerful amnesic drugs (Davis et al 1978; Sitaram et al 1978; Power et al 2003; Bubser et al 2012), while M 1 /M 4 receptor agonists can produce measurable memory enhancing effects in humans and in laboratory animals (Bodick et al 1997; Shekhar et al 2008; Lebois et al 2010; Bubser et al 2014; Galloway et al 2014; Gould et al 2017). In addition to those cognitive effects, we have shown that simulation of M 1 or M 4 receptors can decrease abuse-related effects of cocaine in rodents, including the direct reinforcing effects of cocaine in self-administration assays, and to some extent also “subjective” or conditioned effects, in drug discrimination and place conditioning assays (Thomsen et al 2010a, 2012, 2014; Dencker et al 2012; Dall et al 2017). We therefore wanted to investigate whether M 1 /M 4 receptor stimulation can also facilitate extinction of cocaine seeking, providing multiple mechanisms by which they may be efficacious in the treatment of cocaine addiction.…”
Section: Introductionmentioning
confidence: 99%